Impact of Regulated Deficit Irrigation on Fruit Quality and Postharvest Storage Performance of ‘Cripps Pink’ Apple - Sembok, Wan Zaliha; Singh, Zora (International Society of Horticultural Science, 2010)
This study aimed to develop an irrigation strategy for apples to improve fruit skin colour without adversely affecting postharvest life and quality. Regulated deficit irrigation (RDI) at different levels [(i) 100%, commercial irrigation (CI) (70 L•h-1); (ii) 25% RDI (50 L•h-1); (iii) 50% RDI (35 L•h-1); and (iv) 75% RDI (20 L•h-1)] was applied from 135 days after full bloom (DAFB) continuously for 72 days till harvest. RDI (75%) significantly reduced leaf water potential as compared to CI. RDI (75%) improved fruit skin colour via enhanced accumulation of anthocyanins, increased soluble solids concentration (SSC), fruit firmness and slightly decreased fruit diameter. The RDI fruit (75%) stored for 135 days at 0±0.1°C, 90±2% RH remained firmer and had higher SSC compared to CI fruit. Similarly, RDI fruit (75%) stored for 155 days in controlled atmosphere (CA) comprising of 2.7% O2 + 1.9% CO2 at 0°C had higher SSC and fruit firmness than in CI fruit. In conclusion, RDI (75%) imposed at the late fruit development stage improved the fruit quality of ‘Cripps Pink’ apple at harvest without adversely affecting postharvest quality in cold and CA storage, and also saved irrigation water.